Aplikasi Biochar dan Pupuk Hayati Dalam Meningkatkan Kualitas Lahan Sawah Tadah Hujan Serta Produktivitas Padi di Gunungkidul - Damasus Riyanto; Sugeng Widodo; Sukristiyonubowo Sukristiyonubowo (Seminar Nasional Lahan Suboptimal, 2019)
Riyanto et al, 2019. The Application of Biochar and Biofertilizer for Improving Rainfed Lowland and Rice Productivity on Gunungkidul Regency. pp. 206-215.Managing land resources and improving soil quality are currently urgent and very important for the sustainability of the next generations. Improvements in the quality of rainfed rice fields can be carried out, among others, by application of biofertilizers and biochar. Biofertilizer is a group of living organisms whose activities can improve soil fertility. Biochar is a solid material obtained from the carbonization process of a biomass of agricultural or plantation waste.  The objective of this research was to study the effect of biofertilizer and biochar on availability of N, P, K and C-organic and rice production. The assessment of the application of biological and biochar fertilizers was carried out in the rainfed rice fields of Wareng village, Wonosari district - Gunungkidul regency. The time of implementation was planting season II (February-June 2017) with the treatments: (A) Control (without biological fertilizer and biochar) +100% chemical recommendations fertilizer (Urea 175 kg / ha + NPK 235 kg / ha), (B) Application of Biofertilizer (Agrimeth) 400 gr / ha, without biochar + 100% chemical recommendations fertilizer (C) Application of Biofertilizer (Agrimeth, without biochar and 50% chemical recommendations fertilizer (D) Application biochar rice husk charcoal 2.0 tons /ha, without biological fertilizer and chemical fertilizer 100% recommendation, (E) Application of Biofertilizer (Agrimeth), and biochar 2 t / ha + 100% chemical recommendations fertilizer (F) Application of Biofertilizer (Agrimeth), and biochar 2 t/ha and 50% chemical recommendation fertilizer. Each treatment was repeated 4 times with the farmer as a replication. The experimental design used RCBD (Randomized Complete Block Design) with 4 times replications. The size of the plot followed the size of farmer ownership (On Farm Reserach). The research was shown that the application of Agrimeth biofertilizers and biochar of rice husk charcoal about 2 ton / ha gives a significant effect on the increase of  Milled Rice  production compared to without biofertilizer and biochar. The reduction of inorganic fertilizers by 50% Ponska has no significant effect with the application of 100% recommended  chemical fertilizers if added with the application of Agrimeth and biochar as much as 2 tons / ha. This indicates that the application of Agrimeth biofertilizer on rainfed lowland rice can increase NPK nutrient uptake while the application of rice husk biochar can increase the C-organic content and stimulate the biological activity of paddy soil and reduce the use of NPK inorganic fertilizers. The availability of NPK elements after application with rice husk biochar and Agrimeth biofertilizer showed that the total N content increased by 22.17%, available P and available K increased by 30.19% and 40.09% respectively compared to controls (treatment of local Farmers ) Likewise, the yield of Milled Rice (MRY) increased with the application of a of biochar and biofertilizer by 37.98%, whereas with a single application (only biochar or biofertilizers) only increased between 14.22-20.16% compared to treatment control.